Implementasi Program Edukasi Parlemen DPR RI sebagai Sarana Komunikasi Publik - Rahman, Tedi Fathur; Toruan, Rialdo Rezeky Manogari Lumban; Hamzah, Radja Erland (Petanda: Jurnal Ilmu Komunikasi dan Humaniora, 2025)
Public Relations plays a strategic role in government institutions by fostering two-way communication between the organization and the public. The Public Relations Division of the House of Representatives of the Republic of Indonesia (DPR RI) implements the Parliamentary Education Program as a means of public communication to enhance citizens’ understanding of the duties, functions, authorities, and work mechanisms of the DPR RI. This study aims to analyze the implementation of the Parliamentary Education Program as a public communication strategy based on the Boundary Spanning Theory and Excellence Theory of James E. Grunig. The research employed a qualitative method with a constructivist approach through in-depth interviews with DPR RI Public Relations officials and program participants. The findings reveal that the program effectively serves as a medium of public education through an edutainment approach that combines interactive learning and direct observation. DPR RI’s Public Relations acts as a communication facilitator that bridges the institution and the public through transparent, two-way communication, thereby improving the institution’s image and reducing negative public perceptions. This implementation also strengthens DPR RI’s Public Relations function as a public communication facilitator promoting transparency and accountability.